ANALISIS PENYAMPAIAN PPH PASAL 21 WAJIB PAJAK ORANG PRIBADI DALAM PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI DI KPP PRATAMA TEGALSARI SURABAYA - Astutik, Puji Arfian Widya; Soema Atmadja, Soesilawati (Ekomania, 2023)
The great potential in timely tax payments is very beneficial for the economy and development in Indonesia, and this study aims to find out whether the delivery of individual taxes with the help of tax volunteers is as expected, as the individual tax reports are often ignored by taxpayers and leading to lower tax revenues. The importance of educating taxpayers is something to think about, with the help of tax volunteers, hopefully this will help make taxpayers aware of the importance of paying taxes on time for the prosperity of the Indonesian people. Speaking of implicit taxes is like coercion, because the tax itself is coercive, which has become an obligation of the taxpayer and cannot be challenged for the public good. Can it be done as expected, it is up to the taxpayers who have the knowledge and the will, but as far as the tax return is concerned, the tax volunteers have done as much as possible so that the tax revenue is sufficient to support the development and economy of the country.